2020
DOI: 10.3390/ma13122761
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Large Slump Concrete Made by Post-Filling Coarse Aggregate Mixing Procedure

Abstract: High-performance pumping concrete has been widely used in high-rise building construction because of its superior qualities. However, early cracking problems can occur in cast-in-place pumping concrete, which is due to the excessive use of cement. In this paper, an innovative concrete mixing procedure called “post-filling coarse aggregate concrete” (PFCC) was adopted and applied to large slump concrete. The influence of the post-filling coarse aggregate (PFA) ratio on the mechanical properties of large slump c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The stirrup reinforcement ratio exhibits a noticeable influence on the enhancement of the ultimate shear capacity of the beam. (5) The code GB50010 provides conservative predictions for ultimate shear capacities V u for all tested beam specimens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The stirrup reinforcement ratio exhibits a noticeable influence on the enhancement of the ultimate shear capacity of the beam. (5) The code GB50010 provides conservative predictions for ultimate shear capacities V u for all tested beam specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Originally used for pavement concrete, PFCC is used to solve the problem of aggregate suspension [4] and excessive paste of high-performance concrete, which is critical in meeting the working performance requirement. The post-filling coarse aggregate concrete not only reduces the use of cement [5] but also increases the volume percentage of coarse aggregates, which improves the early-age cracking resistance of concrete [6]. In practical application, it has been found that the strength properties [5] of concrete can also be improved.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, investigations of post-filling coarse aggregate concrete on the structural element in building and bridge engineering have rarely been reported. Jia’s research group has carried out some experimental and theoretical research on the post-filling coarse aggregate concrete (Cao et al, 2020; Hu, 2015; Jia et al, 2017, 2020). It was found that the compressive strength, splitting tensile strength, elastic modulus and flexural strength of the post-filling coarse aggregate concrete with proper post-filling ratio have been improved compared with the reference concrete.…”
Section: Introductionmentioning
confidence: 99%